Factors that Play a Role in Improving Employee Performance - Wulantika, Lita; Widyanti, Armitha (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to see of knowing the factors that play a role in improving employee performance in plantation agencies. The statistical method used in this research is inferential statistics. The type of research in this research is descriptive verification research consisting of multiple linear regression analysis, analysis of the correlation coefficient of product momentum, and the coefficient of determination. The sampling used was simple random sampling consisting of 68 respondents. The data was collected by distributing questionnaires using a 5-point Likert scale. Descriptive method data analysis is done by calculating the mean and continuum line. The data analysis technique used is the path analysis technique. The results showed that leadership, organizational commitment and job satisfaction have an effect on employee performance.